M2+(Ni, Cu, Zn)/Al-LDH Composites with Hydrochar from Rambutan Peel and Study the Adsorption Efficiency for Organic Dyes: 10.32526/ennrj/20/202100218 - Mohadi, Risfidian; Normah, Normah; Palapa, Neza Rahayu; Lesbani, Aldes (Environment and Natural Resources Journal, 2022)
Ni/Al LDH, Cu/Al LDH, and Zn/Al LDH were composed with rambutan peel hydrochar (Hc) and the materials were applied as adsorbent for the removal of methylene blue from aqueous solution, measured using UV-Vis Spectrophotometric method. The preparation of the LDH-Hc composites were proven by XRD, FT-IR, and SEM analysis which showed similar characteristics of the LDH-Hc composites with pure LDH and hydrochar. The methylene blue removal efficiency was optimized by various parameters including adsorption selectivity, adsorption regeneration, pH, contact time, adsorption concentration, and temperature. The adsorption study analysis proved that LDH composited with rambutan peel hydrochar had a selective ability for methylene blue. Zn/Al-hydrochar had the most stable adsorption regeneration ability and adsorbed MB easily after seven regeneration cycles using water solvents and ultrasonic devices. Ni/Al-hydrochar and Cu/Al-hydrochar were effective up to five regeneration cycles for MB removal. The adsorption results showed that the optimal pH for MB adsorption was at pH 6 with an equilibrium adsorption contact time of 100 min and a tendency to follow the pseudo second order kinetic model. Parameter data of concentration and temperature of adsorption was determined using Langmuir and Freundlich equations. The results showed that the adsorption matched the Freundlich isotherm model with the adsorption capacity (qm) of Ni/Al-Hc, Cu/Al-Hc, and Zn/Al-Hc adsorbents reaching 144.928, 175.439, 217.391 mg/g, respectively, with the adsorption process taking place continuously, spontaneously, and endothermically.